H3K14 lactylation exacerbates neuronal ferroptosis by inhibiting calcium efflux following intracerebral hemorrhagic stroke - Tingting Sun; Jian-Nan Zhang; Ting Lan; Lei Shi; Liye Hu; Liyan Yan; Chao Wei; Lisha Hei; Weihua Wu; Zhaoli Luo; Meng Liu; Xingmei Ren; et al. (Cell Death and Disease)
Abstract Inhibiting neuronal ferroptosis is essential for mitigating neural damage and enhancing recovery in central nervous system (CNS) disorders, including intracerebral hemorrhagic stroke (ICH). Lactate accumulation correlates with ICH severity, yet the role of lactate-derived histone lactylation, a novel epigenetic modification, in ferroptosis and its mechanisms is not fully understood. In this study, we aimed to investigate the role of histone lactylation on neuronal ferroptosis in ICH models, both in vitro and in vivo. We discovered elevated lactate and histone lactylation post-ICH in mice, with a significant increase in H3K14la during the early stages of ferroptosis in hemin-challenged primary cortical neurons. Pharmacological or genetic inhibition of H3K14la by targeting lactate dehydrogenase (LDH) enzyme activity effectively suppressed neuronal ferroptosis. We further identified p300/CBP and class I histone deacetylases (HDACs) as the key modifiers of H3K14la in this process. Through chromatin immunoprecipitation-sequencing and RNA-sequencing (RNA-seq) in hemin-treated neurons, we pinpointed the Ca2+-ATPase PMCA2 encoding gene as a direct downstream target of H3K14la. H3K14la/PMCA2 promoted ferroptosis by elevating intracellular calcium levels. In line with our in vitro findings, inhibiting H3K14la/PMCA2 reduced neuronal degeneration and improved functional outcomes in an ICH mouse model induced by intracranial injection of collagenase into the striatum. Taken together, our findings elucidate the role of histone lactylation and PMCA2 in neuronal ferroptosis and implicate that targeting histone lactylation could be a promising therapeutic strategy for ICH and related CNS diseases.